A Comparison of Polyvalent Passive Immunoprotection from Antibodies with Different Immunity Models of Live or Inactivated Vibrio fluvialis in Fish - Huihui Xiao; Pan Cui; Jing Chen; Xiaohui Han; Ziye Ma; Chen Chen; Yong Liu; Xiang Liu (Fishes, 2024)
Polyvalent passive vaccines can act fast in resisting various bacteria with good efficacy, and they have application value in aquaculture. This study prepared live and inactivated Vibrio fluvialis mouse antisera (L-VF-antiserum and I-VF-antiserum), and administered them to goldfish (Carassius auratus) infected with V. fluvialis and Aeromonas hydrophila. The passive protective rates of live and inactivated mouse antisera against V. fluvialis were 60% (p < 0.05) and 40% (p < 0.05), and their passive cross-protective rates against A. hydrophila were 42.86% (p < 0.05) and 35.71% (p < 0.05), respectively. Furthermore, the two mouse antisera could recognize the bacteria in vitro; the content of bacteria in the C. auratus kidney decreased (p < 0.05), the phagocytic activity of C. auratus leukocytes was enhanced (p < 0.05), and the expression of inflammatory genes and activity of antioxidant factors decreased (p < 0.05). Moreover, the kidney, spleen, and intestinal tissue structures were intact, and the apoptosis and DNA damage were decreased (p < 0.05) among the kidney cells. The live V. fluvialis antiserum contained more antibodies against the outer membrane proteins of V. fluvialis than the inactivated mouse antiserum. The immunoprotective abilities of the live V. fluvialis antiserum were higher than those of the inactivated antiserum, and the antiserum of live V. fluvialis immunity demonstrated potential application value as a polyvalent passive immune vaccine in fish.